1999
DOI: 10.1016/s0009-9236(99)80168-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of plasma mycophenolic acid (MPA) and its glucuronide (MPAG) concentrations with antibiotic treatment

Abstract: Clinical Pharmacology & Therapeutics (1999) 65, 159–159; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ciclosporin may also inhibit colonic flora leading to less conversion of MPAG back to MPA. [30,36,39] It is therefore plausible that several concurrent mechanisms contribute to the altered pharmacokinetic profile of MPAG caused by ciclosporin.…”
Section: Discussionmentioning
confidence: 99%
“…Ciclosporin may also inhibit colonic flora leading to less conversion of MPAG back to MPA. [30,36,39] It is therefore plausible that several concurrent mechanisms contribute to the altered pharmacokinetic profile of MPAG caused by ciclosporin.…”
Section: Discussionmentioning
confidence: 99%
“…Such effects result from changes in the intrinsic UGT enzymatic clearance of MPA, and the degree of effect may vary depending on genetic factors. Another mechanism by which drug-drug interactions may affect MPA exposure is by suppression of the EHC pathway by certain antibiotics secondary to loss of glucuronidase activity normally shed by gastrointestinal tract bacteria (17,18). The prime example of a drug that suppresses the EHC pathway is CsA, which, when coadministered with MPA therapy, results in a significant reduction of dosage-adjusted MPA concentrations.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…The extent of MPA reabsorption was similarly decreased by concurrent antibiotic therapy. In healthy volunteers, concomitant treatment with the antibiotic metronidazole was associated with a 36% decrease in oral AUC exposure of MPA [73]. Taken together, the interaction studies with cholestyramine or metronidazole suggested that ∼35% of oral MPA exposure and bioavailability may result from enterohepatic recirculation of MPA.…”
Section: Stabilitymentioning
confidence: 86%